A PROFILE OF COMPARATIVE STUDY OF SOCIO ECONOMIC STATUS OF MANIPURIS INHABITED IN NORTH TRIPURA, UNAKOTI DISTRICT OF TRIPURA AND BARAK VALLEY - Singha, Manindra (International Journal For Research In Business, Management And Accounting, 2020)
Measuring the study area of the Manipuri inhabited areas of above mentioned places right from the Manipuri Culture, Transiting images in study areas of Tripura and Assam, Social structure of Manipuris covering right from the ritual of marriage to death it is found in both the study areas some majors has been changed with the changing scenario of time.